Happily Ever After: The Effect of Identity-Consistency on Product Satiation. Issue 4 (4th August 2015) - Chugani, Sunaina K.; Irwin, Julie R.; Redden, Joseph P.
Abstract : Repeated consumption of products and experiences leads to a reduction in enjoyment over time, a phenomenon that is commonly referred to as "satiation." Three studies show that consumers satiate more slowly to products that are consistent with a currently active identity. Because satiation is a natural human response when consuming a product repeatedly, all consumers are likely to feel the pull downward on their product enjoyment over time. This drop in enjoyment produces dissonance in consumers with an activated identity because reduced enjoyment with identity-consistent products conflicts with their identity. Resisting this drop results in lowered levels of satiation, and these satiation differences are even reflected in subsequent consumption behavior. These results have theoretical implications both for the nascent research area of satiation in consumer behavior and for developing a fuller sense of the relationship between consumer identity and consumption.